Quantification of Temozolomide in Nonhuman Primate Fluids by Isocratic Ultra-High Performance Liquid Chromatography-Tandem Mass Spectrometry to Study Brain Tissue Penetration Following Intranasal or Intravenous Delivery - Peer, Cody J. (Separations, 2016)
A sensitive and selective ultra-high performance liquid chromatography-tandem mass spectrometric method was developed for the quantification of temozolomide (TMZ) in nonhuman primate (NHP) plasma, cerebrospinal fluid (CSF), and brain extracellular fluid (ECF) following microdialysis. Ethyl acetate was used to extract the plasma and CSF samples, using theophylline as the internal standard (IS). ECF samples were diluted with acetonitrile prior to analysis. TMZ was separated on a Waters UPLC® BEH C18 column with an isocratic mobile phase of ammonium acetate (10 mM)-0.1% formic acid/acetonitrile (30:70, v/v) in a positive-ion multi pie reaction monitoring mode (m/z 195.5 →137.6 for TMZ; m/z 181.5→124.2 for IS). The retention time of TMZ and theophylline was 0.45 min with a total run time of 2.5 min. The method was validated over the range from 5–2000 ng/mL in NHP plasma, CSF, and ECF with respect to linearity, accuracy, precision, selectivity, and stability. This method was successfully applied toward the measurement of pharmacokinetic samples following various routes of drug administration.